Identification and Monitoring of Instability in Financial Systems - Włodarczyk, Bogdan; Szturo, Marek (Olsztyn Economic Journal, 2016)
Financial instability is often the result of a positive feedback loop, which is an inseparable element of the functioning of the financial system. The task dealing with identification, modeling and analyzing the causes and effects of such feedback loops requires assuming a systems’ engineering perspective, which is rarely taken into consideration when designing remedial solutions. The aim of the study was to evaluate how it ispossible to identify and monitor the susceptibility of a financial system to potential threats. The popular method of data modeling known as signed directed graphs (SDG) was used. The method is able to pick up information which is not taken into account by a traditional network model of the financial system. It provides essential information about the direction of impact and control between the nodes. Thanks to this technique, it is possible to analyze the potential instability spots of the system.